(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
In order to describe the surrounding reality, the mankind has introduced various normalized quantities. In exchange of goods the unit of measurement expressed as the price of goods or services (money) is commonly used. The analysis of money-goods relation allowed to formulate the principles of market economy